If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = -2(x + 2) Reorder the terms: 3 = -2(2 + x) 3 = (2 * -2 + x * -2) 3 = (-4 + -2x) Solving 3 = -4 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 3 + 2x = -4 + -2x + 2x Combine like terms: -2x + 2x = 0 3 + 2x = -4 + 0 3 + 2x = -4 Add '-3' to each side of the equation. 3 + -3 + 2x = -4 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = -4 + -3 2x = -4 + -3 Combine like terms: -4 + -3 = -7 2x = -7 Divide each side by '2'. x = -3.5 Simplifying x = -3.5
| 7(4n+5)=5(2n+7) | | y(y-3)+6=2y | | G-9.3=9.2 | | 4y-2y+18=12 | | 5n-8n+4= | | 6+7n-49=-85 | | 20m+12=30m-18 | | -2p+6-8p+9= | | 9-5c=12-(6c-7) | | 9(x-3)=63 | | 4+6x-4=3x | | 8=-12+5n | | 3y(y-2)-2y(y-3)=4 | | 500=35-4x | | 4z+5=6z+7 | | -3[w+5]+5w=2[w-6] | | 8+5x=-27 | | -9f+2+8-5f= | | 6-s=18 | | [(2x+1)-5(x-4)]+4=10(x+3) | | 5h-(8+7h)= | | 2(4e)=40 | | 1=3(k+8) | | 5-7f+8f-3= | | 13=z+5 | | 6w+5=29 | | -9-1.1x=6.8 | | x+4x-21= | | (4x-23)+(2x+17)=180 | | -6x-2x+13=-11 | | 3[x+2]+2x=7[x-1]+9 | | 5+0.1Q=20-0.2Q |